Structural Analysis and Load Calculation of CRH380 High-speed Rail Gearbox based on Finite Element - Liu Jie; Liu Shijun; Guo Biao; Guo Jinjin (Jixie chuandong)
Aiming at the crack phenomenon in high- speed gearbox,the force of the suspension gearbox is calculated. The strength analysis of gearbox is carried out by using the finite element software ANSYS Workbench,and the weak position of gearbox is founded and the improvement scheme of the structure is put forward.The improvement scheme of structure is verified by using the simulation software. A basis for the structure design and optimization of high- speed rail gearbox is provided through the research work.